Lean Supply Chain System in Indonesian Banking Industry - Sari, Rini Mulyani; Nugraha, Evan (Technium Social Sciences Journal, 2021)
The goal of this research is to identify, inspect, and assess the existing system, performance, limitations encountered, and lean supply chain solutions that may be used in the banking industry’s account opening process. The qualitative exploratory analytical research approach was utilized, using a sample of state-owned banks such as Bank Mandiri, Bank Negara Indonesia (BNI), and Bank Rakyat Indonesia (BRI). The process of developing a lean supply chain strategy include identifying problems using SIPOC and VSM tools, analyzing problems using VALSAT tools, improving processes using FMEA tools, and controlling processes using SQC tools. The system of account opening that is now in use in the banking industry is partial, the performance of the banking industry’s account opening system is not ideal, some of the issues that have arisen as a result of the banking industry’s account opening system include, among other things, an increase in the number of employees and a lack of ergonomic in the design of the teller machine, and Process Activity Mapping may be used in the banking industry as a lean supply chain strategy